Population structure of the Southeast Asian river catfish Mystus nemurus - Usmani, S.; Tan, S. G.; Siraj, S. S.; Yusoff, K. (Wiley, 2003)
A total of 143 microsatellites were isolated from Mystus nemurus using a 5′ anchored polymerase chain reaction technique or the random amplified hybridization microsatellite method, the first set of microsatellite markers developed for the Southeast Asian river catfish. Twenty polymorphic microsatellite loci were used as markers for population characterization of M. nemurus from six different geographical locations in Malaysia (Perak, Kedah, Johor, UPM, Sarawak and Terengganu). The number of alleles per locus ranged from 2 to 11 with 6.3 as the average number of alleles per locus. Characterization of the populations showed relatively high levels of genetic variation compared with previous studies using allozyme markers. The highest genetic similarity was found between Perak and Kedah, while the highest genetic distance was found between Terengganu and Kedah. The majority of clustering was in accordance with geographical locations and the histories of the populations. Microsatellite analysis indicated that the Sarawak population might be genetically closer to the Peninsular Malaysian populations than has been previously shown by other molecular marker studies.